Rancang Bangun Sistem Peminjaman Laptop dengan Metode Extreme Programming Menggunakan Framework Bootstrap - GOLDIE GUNADI (Universitas Multimedia Nusantara, 2021)
PT Gramedia is a company engaged in the printing industry. Currently, PT Gramedia provides facilities for a number of laptops that can be lent to employees to support their work needs. During the current COVID-19 pandemic, PT Gramedia requires some of its employees to work from home. This results in the increasing need for employees to work devices in the form of laptops. The research conducted aims to design and build a web-based laptop lending information system using the Bootstrap 4 framework, which is intended to help make the data collection and administration process faster, easier and more efficient in terms of time, cost, place and energy. From the results of the research, a system was built according to user needs and was able to solve existing problems. In addition, the resulting system is also more flexible and dynamic and can be accessed from a variety of different types of devices. Index Terms—Bootstrap; extreme programming; information system; laptop rental